Manual "DESCRIBING MY CONTEXT" en la comprensión de textos en inglés, en estudiantes del 2° grado de educación secundaria, de la l.E. "Santa Rosa" de la ciudad de Tarapoto, en el año 2007 - Zelada Mori, Onasis (2008)
The English Language Training-Teaching at the educational lnstitutions of secondary in our country was done before and it is going on now, but, without the suitable methodology, or the educational means, or the appropriate motivation that guarantee the understanding, the comprehension of the significant one and the meaning of the linguistic signs. The trouble with the teachers in charge of the process of the English language Training-Teaching, it is that they just take the school texts from other printed texts in English that are very widely. They get the students get bored without understanding not even the significant one of the linguistic signs, not the terms meaning that are on the texts, in order to get an approving mark, they turn to other people who are qualified to English, other people who does the homework to them, acquitting oneself well next day with the English Teacher, who checks the homework out. With the best intentions of contributing to the solution of this problem, we did research that had as aim to prove the application of the handbook "Describing my Context" will increase meaningfully the text comprehension in English with students of the second year of secondary education of the "Santa Rosa" High School in Tarapoto - 2007. In order to get the proposed aim, we have decided to validate the following hypothesis: lf the handbook "Describing my Context" is applied, then it increases the text comprehension in English with students of the second year of secondary education of the "Santa Rosa" High School in Tarapoto - 2007. In order to confirm the hypothesis, we develop research of applied type with - experimental level of quasi-experimental design of pre-test and post-test with control; group. The sample was made up of 58 students of the second year of the "Santa Rosa" High School, 28 of which were the experimental group and 30 the control; group, who we took them an objective test before and after the experiment. The analysis of the information of the post test to the experimental group and control, through the normal distribution in Z, has allowed confirming the hypothesis, such it is the case that Zc equals 6, 17 is greater than Zt equals 1,64; then Zc is located in the rejection zone, and this is an evidence it has allowed to conclude if the handbook "Describing my Context" is applied, then it gets better the text comprehension in English with students of the second year of secondary education of the "Santa Rosa" High School in Tarapoto - 2007.